Caloric restriction and metformin selectively improved LKB1-mutated NSCLC tumor response to chemo- and chemo-immunotherapy - Gloriana Ndembe; Ilenia Intini; Massimo Moro; Chiara Grasselli; Andrea Panfili; Nicolò Panini; Augusto Bleve; Mario Occhipinti; Cristina Borzi; Marina Chiara Garassino; Mirko Marabese; Simone Canesi; et al. (Journal of Experimental & Clinical Cancer Research, 2024)
Abstract Background About 10% of NSCLCs are mutated in KRAS and impaired in STK11/LKB1, a genetic background associated with poor prognosis, caused by an increase in metastatic burden and resistance to standard therapy. LKB1 is a protein involved in a number of biological processes and is particularly important for its role in the regulation of cell metabolism. LKB1 alterations lead to protein loss that causes mitochondria and metabolic dysfunction that makes cells unable to respond to metabolic stress. Different studies have shown how it is possible to interfere with cancer metabolism using metformin and caloric restriction (CR) and both modify the tumor microenvironment (TME), stimulating the switch from “cold” to “hot”. Given the poor therapeutic response of KRAS mut/LKB1 mut patients, and the role of LKB1 in cell metabolism, we examined whether the addition of metformin and CR enhanced the response to chemo or chemo-immunotherapy in LKB1 impaired tumors. Methods Mouse cell lines were derived from lung nodules of transgenic mice carrying KRASG12D with either functional LKB1 (KRASG12D/LKB1wt) or mutated LKB1 (KRASG12D/LKB1mut). Once stabilized in vitro, these cell lines were inoculated subcutaneously and intramuscularly into immunocompetent mice. Additionally, a patient-derived xenograft (PDX) model was established by directly implanting tumor fragments from patient into immunocompromised mice. The mice bearing these tumor models were subjected to treatment with chemotherapy or chemo-immunotherapy, both as standalone regimens and in combination with metformin and CR. Results Our preclinical results indicate that in NSCLC KRAS mut/LKB1 mut tumors, metformin and CR do enhance the response to chemo and chemo-immunotherapy, inducing a metabolic stress condition that these tumors are not able to overcome. Analysis of immune infiltrating cells did not bring to light any strong correlation between the TME immune-modulation and the tumor response to metformin and CR. Conclusion Our in vitro and in vivo preliminary studies confirm our hypothesis that the addition of metformin and CR is able to improve the antitumor activity of chemo and chemoimmunotherapy in LKB1 impaired tumors, exploiting their inability to overcome metabolic stress.